Exemplars and nudges: Combining two strategies for moral education - Engelen, Bart; Thomas, Alan; Archer, Alfred; van de Ven, Niels (Journal of moral education, 2018)
This article defends the use of narratives about morally exemplary individuals in moral education and appraises the role that 'nudge' strategies can play in combination with such an appeal to exemplars. It presents a general conception of the aims of moral education and explains how the proposed combination of both moral strategies serves these aims. An important aim of moral education is to make the ethical perspective of the subject-the person being educated-more structured, more salient and therefore more 'navigable'. This article argues why and how moral exemplars and nudge strategies are crucial aids in this respect. It gives an empirically grounded account of how the emotion of admiration can be triggered most effectively by a thoughtful presentation of narratives about moral exemplars. It also answers possible objections and concludes that a combined appeal to exemplars and nudges provides a neglected but valuable resource for moral education.